Analysis of Platinum Group Metal (PGM) Topic in Inorganic Chemistry Course in Indonesia - Langitasari, Indah; Mudzakir, Ahmad; Sunyono, Sunyono; Nugraha, Asep Wahyu (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2023)
Platinum Group Metals (PGM) is one of the topics in elemental chemistry in higher education that is important to teach, considering its major role in various industries. PGM is important in various industrial applications, especially as a catalyst in the automotive, electronics, and environmental technology sectors. This study aims to analyze the topic of Platinum Group Metals (PGM) in elemental chemistry teaching in chemistry education study programs in Indonesia with a focus on its relevance, depth, and pedagogical approach. This study is a qualitative descriptive study with a document analysis approach. Data were collected through analysis of Semester Learning Plan documents for inorganic chemistry courses that contain elemental chemistry topics from several universities in Indonesia. Data were analyzed through the following stages: coding, content analysis, and descriptive qualitative. The study's findings indicate that the discussion of PGM on elemental chemistry is still limited and is taught together with other transition elements. The depth of the material also does not reflect the relevance of PGM in industry, modern technology, and sustainable use. This study recommends increasing elemental chemistry learning by teaching PGM topics in more depth as a provision for students to face challenges in the chemical industry. Interdisciplinary teaching approaches and case studies are also needed to strengthen conceptual understanding and student engagement.